Is postmastectomy radiotherapy really needed in breast cancer patients with many positive axillary lymph nodes? - Marinko, Tanja (Radiology and oncology (Ljubljana), 2018)
Postmastectomy radiotherapy (PMRT) improves survival by eliminating potential occult lesions in the chest wall and lymphatic drainage area. Meta-analysis has shown that PMRT reduces mortality and local recurrence of patients with node positive breast cancer (but there is no specific data about the effectiveness of PMRT in a subgroup of patients with a high number of positive axillary lymph nodes (PALN). The aim of the study was to analyse the impact of the number of PALN on local and distant metastasis occurrence, overall survival (OS) and distant metastases free survival (DMFS) in patients treated with PMRT. Patients and methods. We reviewed medical records of 129 consecutive breast cancer patients with PALN, treated at Institute of Oncology Ljubljana with PMRT between January 2003 and December 2004. We grouped patients according to the number of PALN as follows: Group 1 (less than 15 PALN) and Group 2 with more than 15 PALN. All patients received adjuvant systemic therapy according to the clinical guidelines. We analysed number of locoregional (LR) recurrences, distant metastasis, overall survival, progression free survival (PFS) and DMFS. Results. After the median follow-up time of 11.5 years, the Kaplan-Meier survival analysis of PALN showed significantly shorter OS (p = 0.006), shorter PFS (p = 0.002) and shorter DMFS (p 15 PALN. Only one LR was found in the group of patients with more than 15 PALN. In multivariate analysis more than 15 PALN and treatment with anthracycline chemotherapy statistically significantly influenced OS and DMFS. For PFS presence of more than 15 PALN were the only independent factor of shorter survival. Conclusions. Patients with more than 15 PALN have shorter DMFS, PFS and OS as compared to patients with less than 15 PALN, though they receive the same LR treatment. More studies with higher number of patients included are needed to further evaluate our findings.
Keywords: dojke; mastektomija; obsevanje; pozitivne pazdušne bezgavke; radioterapija; rak (medicina)